Polyethylene composition for bottle cap and preparation method thereof

By adjusting the length and sheet thickness distribution of methylene crystal sequence using polyethylene composition and continuous self-nucleation annealing (SSA) method, the problem of large bottle cap opening torque and ring-breaking torque is solved, and the easy opening and low ring-breaking torque of the bottle cap is achieved, which improves the opening experience and sealing performance.

CN119823473APending Publication Date: 2025-04-15CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411831944.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing plastic anti-theft bottle caps have problems with large opening torque and ring-breaking torque when opening, which leads to difficulties in some consumers when unscrewing the bottle caps and the experience of opening the caps is poor.

Method used

Using a polyethylene composition, the composition includes a polyethylene resin, an antioxidant and an acid absorbent, thermal grading is performed by continuous self-nucleation annealing (SSA) method, the methylene crystal sequence length and sheet thickness distribution are adjusted, and a bottle cap with excellent sensory and good physical properties is prepared.

Benefits of technology

It realizes the easy opening of the bottle cap and the low torque of the ring-breaking ring, meets the sealing and use requirements, and improves the opening experience, and is suitable for drinking water bottle caps and non-vapor-containing beverage bottle caps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185750200000071
    Figure BDA0005185750200000071
  • Figure BDA0005185750200000081
    Figure BDA0005185750200000081
  • Figure BDA0005185750200000091
    Figure BDA0005185750200000091
Patent Text Reader

Abstract

The invention provides a polyethylene composition for bottle caps and a preparation method thereof, and relates to the technical field of plastic packaging materials. According to the invention, metallocene polyethylene resin is produced by adopting a supported metallocene catalyst through a vapor phase polymerization process, and 0.02-0.2 part of an antioxidant and 0.05-0.15 part of an acid acceptor are added into the resin to prepare the polyethylene composition. The polyethylene resin disclosed by the invention has the structural characteristics of strong weight-average sequence length, lamellar crystal thickness and distribution uniformity, and the bottle cap prepared from the metallocene polyethylene has the characteristics of excellent sealing performance and sensory performance, good opening performance and lower ring breaking torque, and can be applied to the fields of drinking water bottle caps, non-vapor beverage bottle caps and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic packaging materials, and in particular to a polyethylene composition for bottle caps and a preparation method thereof. Background Art

[0002] Polyethylene plastic anti-theft bottle caps have been widely used in various types of bottled water, herbal tea, juice and carbonated beverages. As part of the food packaging contact material, the sensory performance and hygienic performance of plastic anti-theft bottle caps meet the national standards, requiring no odor, and the physical properties such as sealing performance, impact resistance and drop resistance must meet the requirements of national standards. Plastic anti-theft bottle caps are generally threaded bottle caps that are opened by rotation. Due to the influence of factors such as raw materials, bottle cap specifications, connecting bridge strength and processing technology, many bottle caps have large opening torque and ring breaking torque when opening, which makes it difficult for some consumers to unscrew the bottle caps, resulting in a poor opening experience. At present, polyethylene imported materials still occupy a large share of the domestic bottle cap market, and domestic raw materials still have problems such as unstable performance indicators. Bottle cap manufacturers on the market reported that including some imported raw materials, there is still a high ring breaking torque of the bottle cap. Summary of the invention

[0003] In view of the above problems, the present invention provides a polyethylene composition having excellent sensory properties and good physical properties. The bottle cap prepared from the composition has the characteristics of easy opening and low ring breaking torque while meeting the requirements of sealing and other properties. A preparation method of the composition is also provided.

[0004] One of the objects of the present invention is to provide a polyethylene composition for bottle caps.

[0005] A second object of the present invention is to provide a method for preparing the polyethylene composition for bottle caps.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] In a first aspect, the present invention provides a polyethylene composition, comprising the following raw materials in parts by weight: 100 parts of polyethylene resin, 0.02 to 0.2 parts of antioxidant, and 0.05 to 0.15 parts of acid absorbent.

[0008] The melt mass flow rate (MFR) of the polyethylene resin (test temperature 190°C, load 2.16 kg) is 3.0-6.0 g / 10 min, preferably 3.5-5.5 g / 10 min, more preferably 3.9-5.0 g / 10 min; the density of the polyethylene resin is 0.945-0.958 g / cm 3 , preferably 0.949~0.953g / cm 3The weight average molecular weight of the polyethylene resin tested by GPC method is 6.5×10 4 ~9.6×10 4 , preferably 7.0×10 4 ~8.5×10 4 , the molecular weight distribution is 4.0~5.0.

[0009] In the DSC thermal classification characterization of the polyethylene resin of the present invention using the continuous self-nucleation annealing (SSA) method, the DSC melting curve of the polyethylene resin after thermal classification contains multiple melting peaks, each melting peak basically represents a crystal formed by a class of molecules with very similar branch content, and different melting peaks correspond to the melting of microcrystals of different sizes formed by methylene crystal sequences of different lengths at different temperatures, that is, the longer the crystal sequence structure, the thicker the lamellae thickness corresponding to the molecular chain with less or no branch content, and the thin part of the lamellae corresponds to the molecule with high branch content and irregular chain structure. Different crystal sequence structures correspond to lamellae of different thicknesses, which will eventually affect the mechanical and physical properties of the polyethylene resin.

[0010] The polyethylene resin of the present invention has a suitable distribution of methylene crystal sequence length (or lamella thickness). After thermal classification by continuous self-nucleation annealing (SSA) method, the weight average methylene crystal sequence length calculated by weight average concept is 38.0-43.5, wherein the maximum crystal sequence length is less than 46.5. The corresponding maximum lamella thickness is less than 17.5nm, the relative content of the maximum lamella is not higher than 75%, preferably the content is not higher than 70%, and the weight average lamella thickness calculated by weight average concept is 15.0-16.2nm.

[0011] It has been proved through many experiments and studies that if the weight-average sequence length of the polyethylene resin is not within the specified range, the corresponding lamellae thickness and distribution will also exceed the specified range, resulting in the macroscopic physical properties of the metallocene polyethylene being deficient or failing to meet the final use requirements. Therefore, the above-mentioned specified structural characteristics can ensure that the physical and mechanical properties of the metallocene polyethylene meet the sealing and use requirements of the bottle cap, and at the same time, its tensile force value is within a controllable range, and the prepared bottle cap has the characteristics of easy opening and low ring breaking torque.

[0012] In some embodiments, the polyethylene resin is prepared by the following method:

[0013] Ethylene and α-olefin comonomers are polymerized in the gas phase under the action of metallocene catalysts to produce polyethylene resins;

[0014] The metallocene catalyst comprises a porous support, and a bridged or non-bridged metallocene compound and a co-catalyst supported on the porous support; the porous support is an inorganic oxide, an inorganic chloride or a mixture thereof; the metallocene compound contains one or more η-ligands, and the metal is a 4th, 5th or 6th subgroup metal; the co-catalyst is methylaluminoxane (MAO) or modified methylaluminoxane.

[0015] The porous carrier may be at least one of silica gel, alumina, and molecular sieve. Preferably, the porous carrier is silica gel.

[0016] Preferably, the metallocene compound is a non-bridged organometallic compound, the η-ligand contains a cyclopentadiene derivative group, the cyclopentadiene derivative group includes a cyclopentadienyl group, an indenyl group or a fluorenyl group, the metal is Ti or Zr, the cocatalyst is methylaluminoxane, and the porous carrier is silica gel. Preferably, the η-ligand further contains one or more substituents, and the substituents are C1-C12 alkyl, alkoxy, aryl or aralkyloxy groups.

[0017] Metallocene catalysts can be purchased commercially or prepared by oneself.

[0018] The metallocene catalyst may be a novel broad-distribution metallocene polyethylene catalyst, preferably TH-5B from Xinsu Company.

[0019] The invention adopts Unipol gas phase polymerization process, introduces ethylene and alpha-olefin comonomers into a gas phase fluidized bed reactor, and reacts to generate polyethylene resin under the action of metallocene catalyst.

[0020] The α-olefin comonomer is butene or hexene, preferably hexene; it is used to control the branching degree of the polyethylene molecular chain, and its dosage and distribution on the molecular chain can affect the length of the methylene sequence in the polyethylene molecule, thereby affecting the crystallization behavior and macroscopic physical properties of the polyethylene. Preferably, the molar ratio of the α-olefin comonomer to ethylene is 0.0005 to 0.0010:1.

[0021] In some embodiments, the temperature of gas phase polymerization is 83-89° C., preferably 83-87° C., the pressure of gas phase polymerization is 2.0 MPa-2.3 MPa, preferably 2.1-2.2 MPa, and the ethylene partial pressure is 70-90%, preferably 70-85%. The polymerization temperature and polymerization pressure have a great influence on the average molecular weight of the metallocene polyethylene resin, and then have a significant influence on the melt mass flow rate and physical properties. The above preferred conditions can obtain the above desired metallocene polyethylene resin.

[0022] Preferably, hydrogen is introduced during the gas phase polymerization process to adjust the molecular weight of the polyethylene, and the hydrogen concentration is 500 to 1500 ppm, preferably 600 to 950 ppm.

[0023] Based on 100 parts by mass of polyethylene resin, the amount of antioxidant added is 0.02 to 0.2 parts, such as 0.05, 0.08, 0.1, 0.15, and 0.2 parts. The antioxidant is 1,3,5-tris[4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4 , one or more of 6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylphenyl) phosphite, 3,9-dioctadecyloxy-2,4,8,10-tetraoxy-3,9-diphosphaspiro[5.5]undecane (618) or bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.

[0024] Based on 100 parts by mass of polyethylene resin, the amount of the acid absorber added is 0.05 to 0.15 parts, such as 0.08, 0.10, or 0.12 parts. The acid absorber is one or more of zinc stearate, zinc oxide, magnesium stearate, or calcium stearate.

[0025] In a second aspect, the present invention provides a method for preparing the above polyethylene composition, comprising the following steps:

[0026] The polyethylene resin, antioxidant and acid absorbent are weighed and mixed evenly according to a mass ratio, and then melt-extruded and granulated by a twin-screw extruder to prepare the method.

[0027] Preferably, the method for preparing the polyethylene composition comprises the following steps:

[0028] Add the weighed antioxidant and acid absorbent to the polyethylene resin powder, place in a high-speed mixer and mix evenly, the speed is 1000-1500r / min, and the stirring time is 1-3min;

[0029] The uniformly mixed materials are added to a co-rotating twin-screw extruder with a diameter of 25 mm and an aspect ratio of 40:1 for melt mixing. The extruder barrel is equipped with a vacuum pump for degassing, the vacuum degree is 0.03-0.05 bar, the highest section temperature of the extruder is 160-200°C, the main engine speed of the extruder is 150-350 r / min, the feeding speed is 20-40 r / min, and the polyethylene composition is obtained by extrusion granulation.

[0030] The polyethylene composition used in the present invention has the structural characteristics of strong weight-average sequence length, lamellar thickness and distribution uniformity. The bottle caps prepared using the metallocene polyethylene have excellent sealing performance and sensory performance, good opening performance and low ring breaking torque, and can be applied to drinking water bottle caps, non-carbonated beverage bottle caps and other fields.

[0031] Beneficial effects:

[0032] The polyethylene composition used in the present invention has good sensory properties, no peculiar smell, excellent physical properties and processing properties, and a suitable tensile value between 125 and 135N, which can meet the requirements of compression molding or injection molding processes. The prepared bottle cap has good sealing performance, good opening performance and low ring breaking torque, and is applicable to the fields of bottled drinking water bottle caps, non-carbonated beverage bottle caps, etc.

[0033] The invention obtains a polyethylene resin having a suitable crystal sequence length and a suitable sequence distribution by controlling the hexene monomer content, the ratio of the hexene monomer to ethylene, polymerization process parameters, etc., thereby achieving a suitable tensile force value. The prepared bottle cap has good sealing performance, good opening performance and low ring breaking torque.

[0034] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0036] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0037] The metallocene catalyst was TH-5B from Xinsu Company.

[0038] Antioxidants and acid absorbers are all commercially available products.

[0039] Example 1

[0040] Metallocene catalyst was added to the gas phase polymerization process device, the polymerization temperature was controlled to be 87°C, the polymerization pressure was 2.2MPa, the ethylene partial pressure was 75%, the hydrogen concentration was 856ppm, the molar ratio of hexene to ethylene was 0.0007:1, and the melt index was 4.0g / 10mim and the density was 0.9505g / cm 3 Metallocene polyethylene resin.

[0041] 100 parts of metallocene polyethylene resin powder, 0.05 parts of antioxidant 1,3,5-tris[4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.10 parts of antioxidant bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and 0.10 parts of magnesium stearate were mixed uniformly in a high-speed stirrer at a speed of 1500 r / min for 3 min;

[0042] Extrusion granulation: The uniformly mixed materials are added to a co-rotating twin-screw extruder with a diameter of 25 mm and an aspect ratio of 40:1 for melt mixing. The seventh section of the extruder barrel is equipped with a vacuum pump for degassing, the vacuum degree is 0.03 bar, the highest section temperature of the extruder is 200°C, the main speed of the extruder is 300 r / min, and the feed speed is 35 r / min. The polyethylene composition is obtained by extrusion granulation.

[0043] The obtained polyethylene composition has the following characteristics: melt mass flow rate is 4.0 g / 10 min, density is 0.9505 g / cm 3 The tensile force value is 125N. The weight-average methylene crystal sequence length after DSC thermal classification is 40.1, the weight-average lamellar thickness is 15.5nm, the maximum lamellar thickness is 16.7nm, and the maximum lamellar relative content is 69.8%.

[0044] The polymerization reaction control parameters of the metallocene polyethylene resin in the following Examples 2 to 4 are shown in Table 1, respectively. The preparation steps and methods of material mixing and extrusion granulation in Examples 2 to 4 are the same as those in Example 1.

[0045] Example 2

[0046] Metallocene polyethylene resin powder (MFR 4.5g / 10min, density 0.9510g / cm 3 ), 100 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester 0.06 parts, tris(2,4-di-tert-butylphenyl) phosphite 0.12 parts, and 0.08 parts of zinc stearate.

[0047] Example 3

[0048] Metallocene polyethylene resin powder (MFR is 3.9g / 10min, density is 0.9519g / cm 3 ) 100 parts, 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene 0.04 parts, 3,9-dioctadecyloxy-2,4,8,10-tetraoxy-3,9-diphosphaspiro[5.5]undecane 0.08 parts, zinc oxide 0.10 parts.

[0049] Example 4

[0050] Metallocene polyethylene resin powder (MFR 4.8g / 10min, density 0.9504g / cm 3 ) 100 parts, antioxidant N, N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine 0.15 parts, calcium stearate 0.10 parts.

[0051] Comparative Example 1

[0052] The polymerization reaction control of the metallocene polyethylene resin powder of Comparative Examples 1 to 3 is shown in Table 3. The preparation steps and methods of mixing the materials and extruding granulation of Comparative Examples 1 to 3 are the same as those of Example 1.

[0053] Metallocene polyethylene resin powder (MFR is 2.5g / 10min, density is 0.9496g / cm 3 ), 100 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester 0.05 parts of antioxidant, 0.10 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.05 parts of zinc stearate.

[0054] Comparative Example 2

[0055] Metallocene polyethylene resin powder (MFR is 6.8g / 10min, density is 0.9535g / cm 3 ), 100 parts of antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.08 parts, 3,9-dioctadecyloxy-2,4,8,10-tetraoxy-3,9-diphosphaspiro[5.5]undecane 0.08 parts, and calcium stearate 0.08 parts.

[0056] Comparative Example 3

[0057] Metallocene polyethylene resin powder (MFR 4.2g / 10min, density 0.9557g / cm 3 ), 100 parts of 1,3,5-tris[4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.10 parts of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and 0.10 parts of magnesium stearate.

[0058] Comparative Example 4

[0059] Commercially available high-density polyethylene 1, MFR 7.8g / 10min, density 0.9563g / cm 3 .

[0060] Performance Testing:

[0061] The physical properties and bottle cap properties of the polyethylene compositions prepared in the examples and comparative examples are shown in Tables 1 to 4.

[0062] The test method is tested in accordance with the relevant national standards and industry standards:

[0063] Melt flow rate (MFR) is carried out according to GB / T 3682.1-2018;

[0064] Density is in accordance with GB / T 1033.2-2010;

[0065] Tensile force test method: The specimen is TYPE IV in ASTM D 638, with a thickness of 1 mm and a tensile speed of 200 mm / min.

[0066] The length and distribution of the crystal sequence were tested by DSC continuous self-nucleation annealing (SSA) thermal classification method. The specific conditions are as follows: weigh about 5 mg of the sample, put it into the DSC instrument, first heat it to 170°C at a rate of 50°C / min, keep it constant for 5 minutes to eliminate the thermal history, then reduce it to 0°C at a rate of 25°C / min and keep it constant for 3 minutes; then heat it to the following series of temperatures at a rate of 25°C / min: 125°C, 120°C, 115°C, 110°C, 105°C, 100°C, 95°C, 90°C, 85°C, 80°C, keep it constant for 3 minutes, then reduce it to 25°C at a rate of 25°C / min and keep it constant for 3 minutes; finally heat it to 170°C at a rate of 5°C / min to obtain the multiple melting endothermic peaks of the sample.

[0067] The thickness of each fraction was calculated by the Gibbs-Thomson equation (Equation (1)), and the relative percentage of each fraction was obtained by the area of ​​each melting peak using computer peak analysis technology.

[0068] The crystalline sequence length of each fraction was calculated by referring to the working curve of melting temperature and sequence length in ethylene copolymer given by Keating et al. The number average crystalline sequence length (Ln) and weight average crystalline sequence length (Lw) of each fraction were calculated by equation (2) and equation (3), respectively, and the Z average crystalline sequence length (Lw) of each fraction was calculated by equation (4). Z ), and the weight-average and Z-average distribution coefficients (I) and (I) of the crystallizable sequence length of the sample are calculated using equations (5) and (6). z ). The larger I is, the wider the distribution of the length of the crystallizable sequence of the sample is, which corresponds to a more random distribution of short chain branches in the molecular structure.

[0069]

[0070] The odor test is to place 50g of the sample in a 1000ml wide-mouth bottle with a stopper, place it in an oven at 80℃ for 2h, cool it for 0.5h, select six people with experience in odor evaluation to smell it, and make a grade evaluation according to the evaluation criteria in Table 5.

[0071] Table 5 Evaluation criteria

[0072] grade Judging Criteria 1 Hard to feel, no obvious difference compared with the blank sample 2 Can be felt, but not pungent 3 Can be clearly felt, unpleasant odor 4 Pungent 5 Very pungent 6 Unbearable

[0073] Table 1 Performance test results of the embodiment

[0074]

[0075] Table 2 Performance of Example Bottle Cap (3025 Type Bottle Cap)

[0076]

[0077] Table 3 Comparative Example Performance Test Results

[0078]

[0079] Table 4 Performance of comparative bottle caps (3025 type bottle caps)

[0080]

[0081]

[0082] The MFR of comparative example 1 is relatively low, the processing fluidity is slightly poor, the molded bottle cap part has defects, and the sealing performance is insufficient. Its weight-average sequence length is lower than the range specified by the present invention; comparative example 2 has flash, and the maximum lamella thickness and its relative content are both higher than the specified range, and its tensile force value is relatively high; the weight-average sequence length, the maximum crystal sequence length, the maximum lamella thickness and its relative content of comparative example 3 are all beyond the specified range, so its tensile force value is high and cannot meet the performance requirement of easy opening of the bottle cap.

[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A polyethylene composition for bottle caps, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polyethylene resin, 0.02 to 0.2 parts of antioxidant, and 0.05 to 0.15 parts of acid absorbent; The melt mass flow rate of the polyethylene resin at 190°C and a load of 2.16 kg is 3.0 to 6.0 g / 10 min; the density of the polyethylene resin is 0.945 to 0.958 g / cm 3 ; The weight average molecular weight of polyethylene resin is 6.5×10 4 ~9.6×10 4 , molecular weight distribution is 4.0~5.0; The weight-average methylene crystal sequence length after DSC thermal classification is 38.0-43.5, wherein the maximum crystal sequence length is less than 46.5; the weight-average lamellae thickness is 15.0-16.2nm, wherein the maximum lamellae thickness is less than 17.5nm, and the relative content of the maximum lamellae is not higher than 75%.

2. The polyethylene composition for bottle caps according to claim 1, characterized in that: The polyethylene resin is prepared by the following method: Ethylene and α-olefin comonomers are polymerized in the gas phase under the action of metallocene catalysts to produce polyethylene resins; The metallocene catalyst comprises a porous carrier, and a bridged or non-bridged metallocene compound and a co-catalyst supported on the porous carrier; the porous carrier is an inorganic oxide, an inorganic chloride or a mixture thereof; the metallocene compound contains one or more η-ligands, and the metal is a 4th, 5th or 6th subgroup metal; and the co-catalyst is methylaluminoxane or modified methylaluminoxane.

3. The polyethylene composition for bottle caps according to claim 2, characterized in that: The α-olefin comonomer is butene or hexene, preferably hexene.

4. The polyethylene composition for bottle caps according to claim 2, characterized in that: The molar ratio of the α-olefin comonomer to ethylene is 0.0005 to 0.0010:

1.

5. The polyethylene composition for bottle caps according to claim 2, characterized in that: The temperature of gas phase polymerization is 83-89°C, the pressure of gas phase polymerization is 2.0MP-2.3MPa, and the ethylene partial pressure is 70-90%.

6. The polyethylene composition for bottle caps according to claim 2, characterized in that: Hydrogen is introduced during the gas phase polymerization process to adjust the molecular weight of the polyethylene. The hydrogen concentration is 500 to 1500 ppm, preferably 600 to 950 ppm.

7. The polyethylene composition for bottle caps according to claim 1, characterized in that: The antioxidant is 1,3,5-tris[4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, 1,3,5-trimethyl-2,4 , one or more of 6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylphenyl) phosphite, 3,9-dioctadecyloxy-2,4,8,10-tetraoxy-3,9-diphosphaspiro[5.5]undecane (618) or bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.

8. The polyethylene composition for bottle caps according to claim 1, characterized in that: The acid absorber is one or more of zinc stearate, zinc oxide, magnesium stearate or calcium stearate.

9. A method for preparing the polyethylene composition for bottle caps according to any one of claims 1 to 8, characterized in that: The following steps are involved: The polyethylene resin, antioxidant and acid absorbent are weighed and mixed evenly according to a mass ratio, and then melt-extruded and granulated by a twin-screw extruder to prepare the method.

10. The preparation method according to claim 9, characterized in that: The method comprises the following steps: Add the weighed antioxidant and acid absorbent to the polyethylene resin powder, place in a high-speed mixer and mix evenly, the speed is 1000-1500r / min, and the stirring time is 1-3min; The uniformly mixed materials are added to a co-rotating twin-screw extruder for melt mixing. The extruder barrel is equipped with a vacuum pump for degassing, the vacuum degree is 0.03-0.05 bar, the highest section temperature of the extruder is 160-200°C, the main engine speed of the extruder is 150-350r / min, the feed speed is 20-40r / min, and the polyethylene composition is obtained by extrusion granulation.